Clinical and laboratory profile of juvenile-onset systemic sclerosis in a Brazilian cohort. Issue 1 (February 2019) - Sampaio-Barros, Percival D; Bortoluzzo, Adriana B; Del Rio, Ana Paula T; Luppino-Assad, Ana Paula; Andrade, Danieli CO; Marques-Neto, João Francisco
Objective: To characterize the clinical and laboratory profile of juvenile-onset compared to adult-onset systemic sclerosis in a large Brazilian cohort. Methods: Retrospective analysis of a cohort of 1016 systemic sclerosis patients followed at the Scleroderma Outpatient Clinic from two referral university centers in Brazil. Patients were classified as systemic sclerosis according to the 1980 American College of Rhaumatology (ACR) criteria. Juvenile-onset systemic sclerosis was defined if age at onset was <16 years. Results: Thirty-one (3.1%) patients were classified as juvenile-onset systemic sclerosis. These patients were predominantly females (90.3%), Caucasians (71.0%), and presented diffuse systemic sclerosis (51.6%), with mean age at onset of 12.71 years. Compared to the adult-onset patients, juvenile onset was associated with diffuse systemic sclerosis (p < 0.001), calcinosis (p < 0.001), myositis (p = 0.050), and lower frequency of interstitial lung disease (p = 0.050), pulmonary hypertension (p = 0.035), and esophageal (p = 0.005) involvement. Conclusion: Juvenile-onset systemic sclerosis characterized a distinct clinical pattern in this large series of systemic sclerosis patients, since it was predominantly associated with diffuse systemic sclerosis without significant organ involvement.